Changes in the pharyngeal airway after different orthognathic procedures for correction of class III dysplasia - Mohammad Saleh Khaghaninejad; Leila Khojastehpour; Hossein Danesteh; Mehdi Changizi; Farzaneh Ahrari (SpringerOpen, 2022)
Abstract Objective This study was conducted to compare changes in pharyngeal airway after different orthognathic procedures in subjects with class III deformity. Methods The study included CBCT scans of 48 skeletal class III patients (29 females and 19 males, mean age 23.50 years) who underwent orthognathic surgery in conjunction with orthodontic treatment. The participants were divided into three groups of 16, as follows: Group 1, mandibular setback surgery; group 2, combined mandibular setback and maxillary advancement surgery; and group 3, maxillary advancement surgery. CBCT images were taken 1 day before surgery (T0), 1 day (T1), and 6 months (T2) later. The dimensions of the velopharynx, oropharynx, and hypopharynx were measured in CBCT images. Results In all groups, there was a significant decrease in airway variables immediately after surgery, with a significant reversal 6 months later (P < 0.05). In subjects who underwent maxillary advancement, the airway dimensions were significantly greater at T2 than the T0 time point (P < 0.05), whereas in the mandibular setback and bimaxillary surgery groups, the T2 values were lower than the baseline examination (P < 0.05). The alterations in airway variables were significantly different between the study groups (P < 0.05). Conclusions The mandibular setback procedure caused the greatest reduction in the pharyngeal airway, followed by the bimaxillary surgery and maxillary advancement groups, with the latter exhibiting an actual increase in the pharyngeal airway dimensions. It is recommended to prefer a two-jaw operation instead of a mandibular setback alone for correction of the prognathic mandible in subjects with predisposing factors to the development of sleep-disordered breathing.